Contemporary research on business and management : proceedings of the International Seminar of Contemporary Research on Business and Management (ISCRBM 2019), 27-29 November, 2019, Jakarta, Indonesia /: proceedings of the International Seminar of Contemporary Research on Business and Management (ISCRBM 2019), 27-29 November, 2019, Jakarta, Indonesia. (2020) - Unknown
No abstract available